EXPLORING STUDENTS’ LEARNING STRATEGIES IN SPEAKING PERFORMANCE - Wael, Ahmad; Asnur, Muhammad Nur Ashar; Ibrahim, Ibrahim (International Journal of Language Education, 2018)
This article aims to explore learning strategies used by students in speaking performance. To identify the types of learning strategies were adopted by the students of English department in learning to speak, the authors prepared journal logs with specific questions related to learning strategies. The researchers used qualitative design in this research. The result of this research showed that students of the third semester of English department frequently used memory strategies in learning speaking. The second was metacognitive strategies followed by social strategy in the third rank. The fourth was affective strategies and compensation strategies in the fifth rank and followed by cognitive strategy in the sixth rank. Furthermore, the other factors also influence students? learning strategies in learning speaking such as psychological factor, the role of teacher, task, environment and social factors. The roles of the lecturer as a feedback provider, a participant, and a prompter.